Intestinal helminth Schyzocotyle acheilognathi Yamaguti, 1934 infection ameliorate lipid metabolism of grass carp (Ctenopharyngodon idella) through immune and gut microbiota regulation - Yang, Xiaoao; Zhu, Denghui; Li, Wenxiang; Fu, Peipei (Frontiers in Microbiology, 2025)
Fats have been widely applied in aquaculture to promote growth performance and substitute partial protein in fish feeds. However, excessive dietary fat levels induce metabolic disorders harming the health of cultured fish. Helminth infection in mammals was inversely correlated with metabolic syndrome, but its effect in aquatic animals is unknown yet. Here, we evaluated the impacts of Schyzocotyle acheilognathi infection on lipid metabolism of grass carp fed with high-fat diet (HFD). By comparison with the uninfected grass carp, helminth infection significantly increased the concentration of high-density lipoprotein (HDL) and condition factor (CF), and significantly decreased the concentration of low-density lipoprotein (LDL), the activity of AST, perimeter ratio (PR) and the thickness of muscularis mucosa (MM). Helminth infection also significantly lowered the lipid accumulation in liver, which may attribute to the significant up-regulated expression levels of apolipoprotein E (ApoE) and down-regulated expression of peroxisome proliferator-activated receptor-gamma (PPAR-γ) and lipoprotein lipase (LPL). Meanwhile in the grass carp infected by tapeworm, there was significant down-regulated expression of pro-inflammatory genes, interleukin-1beta (IL-1β) and tumor necrosis factor-alpha (TNF-α), and significant up-regulated expression of anti-inflammatory genes, transforming growth factor-beta 1 (TGF-β1) and interleukin-10 (IL-10). 16S rDNA sequencing results showed that helminth infection didn’t affect the α diversity of the intestinal microbiota, but increased the relative abundance of Cetobacterium, and significantly changed the structure of intestinal microbiota by PERMANOVA analysis. Correlation analysis showed the relative abundance of Cetobacterium was significant positively correlated with the helminth infection in grass carp fed HFD. PICRUST2 analysis indicated that several lipid metabolism-related pathways were significantly altered after helminth infection. Consequently, the above results indicated that tapeworm infection could ameliorate abnormal lipid metabolism through immune and gut microbiota regulation.